2011
DOI: 10.5541/ijot.166
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulations of a Prechamber Autoignition Engine Operating on Natural Gas

Abstract: At our laboratory extensive research has been conducted on the conversion of conventional Diesel cogeneration engines to operation on natural gas and biogas. In the framework of this research, a numerical simulation of a prechamber autoignition gas engine has been performed based on an experimental test case. With a simplified finiterate/eddy-dissipation model for the combustion of natural gas, it was possible to properly reproduce the experiment considering the combustion duration, ignition timing and overall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 12 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…Several prechamber-specific CFD cases have been reported in the past, primarily with the KIVA and FLUENT software packages. Of these cases it has been typical practice to use greatly reduced single-digit equation reaction mechanisms while , if modelled, has been modelled with a form of the Zeldovich mechanism [43][44][45][46][47][48]. More elaborate models using a dedicated multi-step ignition model or a larger mechanism have been used but considering current capabilities, the treatment of chemistry in prechamber-specific cases can be improved [49][50].…”
Section: Previous Prechamber Cfd Modellingmentioning
confidence: 99%
“…Several prechamber-specific CFD cases have been reported in the past, primarily with the KIVA and FLUENT software packages. Of these cases it has been typical practice to use greatly reduced single-digit equation reaction mechanisms while , if modelled, has been modelled with a form of the Zeldovich mechanism [43][44][45][46][47][48]. More elaborate models using a dedicated multi-step ignition model or a larger mechanism have been used but considering current capabilities, the treatment of chemistry in prechamber-specific cases can be improved [49][50].…”
Section: Previous Prechamber Cfd Modellingmentioning
confidence: 99%
“…23 Despite that, the understanding of pre-chamber combustion and the role of the jet (thermal, chemical, and turbulence generation) remains incomplete. 18,24 A large pre-chamber volume contains a larger trapped mass, 2527 thus enhancing the pre-chamber pressure build-up. The nozzle exit area (diameter and number of nozzles) 28 influences the pre-chamber pressure build-up, jets’ temperature, composition, turbulence, efficiency, and pollutant formations 2,21,25,28 ; Shah et al 25 found that large pre-chamber volume combined with small nozzle diameter yield shorter combustion duration with enhanced engine efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…When compared to the number of experimental tests already carried out, the amount of numerical studies involving prechambers is relatively small. One of them was developed by Heyne, Millot and Favrat [4], who simulated a prechamber autoignition gas engine using the commercial code Fluent. Jamrozik, Tutak, Kociszewski and Sosnowski [5] also presented their results for a numerical simulation of two-stage combustion in SI engine with prechamber, using KIVA-3V code.…”
Section: Introductionmentioning
confidence: 99%